Traditional Chinese Medicine Shi-Bi-Man ameliorates psoriasis via inhibiting IL-23/Th17 axis and CXCL16-mediated endothelial activation - Chenyang Zhang; Xinran Cao; Lixin Zhao; Zitong Ni; Haojie Du; Jiao Qu; Jianxia Zhu; Haiyan Sun; Yang Sun; Zijun Ouyang (BMC, 2024)
Abstract Background Psoriasis is a chronic inflammatory genetic disease, mainly manifesting in the skin. Conventional therapies, such as glucocorticosteroids and corticosteroids, have adverse effects that limit drug use. Hence, it is imperative to identify a new therapeutic strategy that exhibits a favorable safety profile. Shi-Bi-Man (SBM) is a safe herbal supplement sourced from various natural plants, including ginseng, angelica sinensis, polygonum multiflorum, and aloe vera. Purpose We aimed to find a potential treatment for psoriasis and investigate the underlying mechanism through which SBM alleviates psoriatic-like skin inflammation in mice. Methods We investigated the effects of supplementing with SBM through intragastric administration or smear administration in a murine model of imiquimod-induced psoriasis. The changes in body weight and Psoriasis Area and Severity Index (PASI) score were recorded throughout the entire process. Additionally, we used hematoxylin-eosin staining to observe the skin structure and performed single-cell RNA sequencing to explore the underlying mechanism of SBM in influencing the psoriasis-like phenotype. Immunofluorescence was conducted to verify our findings. Furthermore, reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was employed to investigate the impact of Tetrahydroxy stilbene glycoside (TSG) on the expression levels of IL23 in HaCaT cells. Results SBM remarkably alleviated the psoriasis-like phenotype by inhibiting IL-23/Th17 cell axis. Single-cell RNA sequencing analysis revealed a decrease in the expression of Il17 and Il23 in keratinocytes and T cells, concomitant with a reduction in the proportion of Th17 cells. Meanwhile, the activation of endothelial cells was inhibited, accompanied by a decrease in the expression of Cxcl16. In vitro, the addition of TSG to HaCaT cells resulted in significant suppression of IL23 expression stimulated by tumor necrosis factor-alpha (TNF-α).